Pharmacological effects and the related mechanism of scutellarin on inflammation-related diseases: a review - Zhou, Yang; Gu, Chenlin; Zhu, Yan; Zhu, Yuting; Chen, Yutong; Shi, Li; Yang, Yang; Lu, Xin; Pang, Hanqing (Frontiers in Pharmacology, 2024)
Inflammation is a biological response of multicellular organisms caused by injuries, pathogens or irritants. An excessive inflammatory response can lead to tissue damage and various chronic diseases. Chronic inflammation is a common feature of many diseases, making the search for drugs to treat inflammation-related diseases urgent. Scutellarin, a natural flavonoid compound, is widely used in the treatment of various inflammation-related diseases for its anti-inflammatory, anti-oxidant and anti-cancer activities. Scutellarin can inhibit key inflammatory pathways (PI3K/Akt, MAPK, and NF-κB, etc.) and activate the anti-oxidant related pathways (Nrf2, ARE, ect.), thereby protecting tissues from inflammation and oxidative stress. Modern extraction technologies, such as microwave-assisted, ultrasound assisted, and supercritical fluid extraction, have been utilized to extract scutellarin from Scutellaria and Erigeron genera. These technologies improve efficiency and retain biological activity, making scutellarin suitable for large-scale production. Scutellarin has significant therapeutic effects in treating osteoarthritis, pulmonary fibrosis, kidney injury, and cardiovascular diseases. However, due to its low bioavailability and short half-life, its clinical application is limited. Researchers are exploring innovative formulations (β-cyclodextrin polymers, triglyceride mimetic active ingredients, and liposome precursors, etc.) to improve stability and absorption rates. Despite these challenges, the potential of scutellarin in anti-inflammatory, anti-oxidant, and anti-cancer applications remains enormous. By optimizing formulations, exploring combination therapies, and conducting in-depth mechanistic research, scutellarin can play an important role in treating various inflammatory diseases, providing patients with more and effective treatment options.